Solar battery cell, manufacturing method of the same, and solar battery module
Patent Information
- Application Number
- JP2023127025
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0014】 本発明によれば、優れた発電特性を有し、かつ耐熱性の高い、ペロブスカイト型の太陽電池セルおよびその製造方法、ならびに太陽電池モジュールが提供される。
Smart Images

Figure 2025022445000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solar cell, a manufacturing method thereof, and a solar cell module. [Background technology]
[0002] Solar cells that use metal halide perovskite organic compounds in the active layer are generally called perovskite solar cells, and many of the manufacturing processes can be carried out by coating solutions containing organic or inorganic substances. Therefore, they can be manufactured at low cost. 2 It has been reported that the energy conversion efficiency exceeds 25% in a small area of less than 100 nm, and the performance is also very promising. Furthermore, the band gap of the perovskite solar cell can be easily adjusted by changing the composition of the active layer. Therefore, it is also attracting attention in the fabrication of tandem multijunction solar cells.
[0003] A known configuration of the solar cell of such a perovskite solar cell is a laminated structure in the order of a glass substrate with a transparent electrode, a hole transport layer, an active layer containing a triple cation lead halide perovskite compound or the like, an electron transport layer, and a metal electrode. In addition, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (hereinafter also referred to as "bathocuproine" or "BCP") is known as a material for the electron transport layer. Bathocuproine has a high affinity with metal electrodes (especially silver electrodes) and is known as an electron transport material with excellent electrical contact.
[0004] The above-mentioned bathocuproine has a HOMO of 3.5 eV and a LUMO of 7.0 eV based on the vacuum level in a single substance. In other words, bathocuproine is a substance with an extremely wide band gap. Therefore, when bathocuproine is used in the electron transport layer, it is possible to prevent the intrusion of holes generated in the active layer into the cathode side. On the other hand, bathocuproine also blocks the flow of electrons from the active layer side to the cathode side. However, it has been reported that when silver is used as the cathode material, the silver creates an intra-band level in the electron transport layer, and electrons travel through this level, resulting in good electrical properties (for example, Non-Patent Document 1). It has also been reported that such diffusion of silver easily occurs in bascuproine at room temperature (Non-Patent Document 2). [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] CJ Huang et al., “Effect of Energy States in Buffer Layer on Organic Solar Cells Output Performance,” ECS Solid State Lett., vol. 2, no. 1, pp. Q5-Q7, [Non-Patent Document 2] Z. Ying et al., “Charge-transfer induced multifunctional BCP:Ag complexes for semi-transparent perovskite solar cells with a record fill factor of 80.1%,” J. Mater. Chem. A, vol. 9, no. 20, pp. 12009-12018, 2021 Summary of the Invention [Problem to be solved by the invention]
[0006] However, a major issue with perovskite solar cells containing the above-mentioned bathocuproine as an electron transport material is that they have inferior heat resistance compared to existing solar cells composed of inorganic semiconductor crystals. The glass transition temperature of bathocuproine is 83°C. Therefore, there is an issue that sufficient power generation performance cannot be obtained when applied to outdoor solar cells or solar cells for automobiles. Therefore, there is a demand for a compound that is stable even at high temperatures and is suitable as an electron transport material.
[0007] Here, 9-bis(naphthalene-2-yl)-4,7-diphenyl-1,10-phenanthroline (hereinafter also referred to as "β-NBPhen") and 9-bis(naphthalene-1-yl)-4,7-diphenyl-1,10-phenanthroline (hereinafter also referred to as "α-NBPhen") have a proven track record in organic electroluminescence elements, and are known to have higher thermal stability than bathocuproine. Therefore, it is conceivable to use these as materials for the electron transport layer of perovskite solar cells. However, in general, β-NBPhen and α-NBPhen have a weak interaction with a metal electrode. Therefore, when an electron transport layer containing β-NBPhen or α-NBPhen is merely formed by a conventional method, the series resistance between the electron transport layer and the cathode tends to be large, and the initial characteristics (fill factor) of the solar cell tends to be lower than when bathocuproine is used.
[0008] Therefore, an object of the present invention is to provide a perovskite solar cell having excellent power generation characteristics and high heat resistance, a method for manufacturing the same, and a solar cell module. [Means for solving the problem]
[0009] The present invention provides a solar cell having an active layer containing a metal halide perovskite compound, an electron transport layer disposed on the active layer, and a cathode layer disposed adjacent to the electron transport layer, wherein the electron transport layer contains 9-bis(naphthalen-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalen-2-yl)-4,7-diphenyl-1,10-phenanthroline, and has a bond promotion region in a region adjacent to the cathode layer for promoting electrical bond with the cathode layer.
[0010] The present invention also provides a solar cell module including the solar cell described above and a sealing material that covers the solar cell.
[0011] The present invention further provides a method for producing a solar cell, comprising the steps of: preparing an active layer containing a metal halide perovskite compound; forming an electron transport layer on the active layer; and forming a cathode layer adjacent to the electron transport layer, wherein the step of forming the electron transport layer comprises the steps of forming an electron transport material-containing region containing 9-bis(naphthalen-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalen-2-yl)-4,7-diphenyl-1,10-phenanthroline; and forming a junction-promoting region on the electronic material-containing region, the junction-promoting region containing at least one compound selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum.
[0012] The present invention also provides a method for manufacturing a solar cell, comprising the steps of: preparing an active layer containing a metal halide perovskite compound; forming an electron transport layer on the active layer; and forming a cathode layer adjacent to the electron transport layer, wherein the step of forming the electron transport layer comprises the step of co-depositing 9-bis(naphthalene-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalene-2-yl)-4,7-diphenyl-1,10-phenanthroline with a metal material and / or a bond promotion material to form a bond promotion region, and the bond promotion material is a compound selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum.
[0013] The present invention further provides a method for manufacturing a solar cell, the method including the steps of: preparing an active layer containing a metal halide perovskite compound; forming an NBPhen layer containing 9-bis(naphthalen-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalen-2-yl)-4,7-diphenyl-1,10-phenanthroline on the active layer; forming a metal material layer containing a metal material adjacent to the NBPhen layer; and, after the step of forming the metal material layer, heating the NBPhen layer and the metal material layer to a temperature of 60°C or higher and 180°C or lower. Effect of the Invention
[0014] According to the present invention, there are provided a perovskite solar cell having excellent power generation characteristics and high heat resistance, a method for producing the same, and a solar cell module. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic diagram showing the structure of a solar cell according to one embodiment of the present invention. [Diagram 2]FIG. 2A is a schematic diagram showing the configuration of the electron transport layer according to the first and third embodiments, and FIG. 2B is a schematic diagram showing the configuration of the electron transport layer according to the second embodiment. [Diagram 3] FIG. 3 shows the absorbance measurements of β-NBPhen, Liq, and silver alone or when layered. [Figure 4] 4A to 4F are process diagrams showing a method for producing a solar cell in an example. [Diagram 5] FIG. 5 is an exploded view of the solar cell produced in the example. [Figure 6] FIG. 6 is a graph showing the current-voltage characteristics of the solar cells fabricated in Example 1-1 and Comparative Examples 1-1 to 1-3. [Figure 7] FIG. 7 is a graph showing the energy conversion efficiency, open circuit voltage, short circuit current density, and fill factor of the cells produced in Example 1-1 and Comparative Examples 1-1 to 1-4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In this specification, a numerical range indicated with "~" means a numerical range including the numerical values written before and after "~".
[0017] FIG. 1 shows an example of the structure of a solar cell according to an embodiment of the present invention. As shown in FIG. 1, a solar cell 10 has an active layer 14 containing a metal halide perovskite compound, an electron transport layer 15 disposed on one side of the active layer 14, and a cathode layer 16 disposed adjacent to the electron transport layer 15. A hole transport layer 13, an anode (transparent electrode) 12, and a transparent substrate 11 are disposed in this order on the other side of the active layer 14. In the solar cell 10, sunlight is incident from the transparent substrate 11 side, and the metal halide perovskite compound (hereinafter also simply referred to as "perovskite compound") in the active layer 14 is excited by the incident light. Then, electrons generated by the excitation of the perovskite compound move to the cathode layer 16 side via the electron transport layer 15, and holes move to the anode 12 side via the hole transport layer 13, generating an electromotive force. The solar cell 10 of this embodiment may include other layers and configurations as long as the object and effect of this embodiment are not impaired.
[0018] Here, the electron transport layer 15 of the solar cell 10 of this embodiment contains α-NBPhen and / or β-NBPhen. The electron transport layer 15 has a bond-promoting region (not shown) adjacent to the cathode layer 16 for promoting electrical bond with the cathode layer 16. Solar cells including such an electron transport layer 15 will be described taking the following three aspects as examples. However, this embodiment is not limited to these aspects.
[0019] (1) First aspect As described above, the solar cell 10 of the first embodiment has a structure in which the transparent substrate 11 / anode 12 / hole transport layer 13 / active layer 14 / electron transport layer 15 / cathode layer 16 are laminated in this order. A partially enlarged view of the electron transport layer 15 of this embodiment is shown in FIG. 2A. The electron transport layer 15 of this embodiment has a C 60 Three regions are arranged in order: a fullerene-containing region 15a containing a fullerene or its derivative, an electron transport material-containing region 15b containing the electron transport material α-NBPhen and / or β-NBPhen, and a bond-promoting region 15c containing a bond-promoting material.
[0020] The solar cell 10 has good heat resistance and can be used in high temperature environments because it uses α-NBPhen and / or β-NBPhen as the electron transport material. As described above, in conventional solar cells using α-NBPhen and / or β-NBPhen, the series resistance between the electron transport layer and the cathode tends to be large, and the initial characteristics of the solar cell tend to be poor. In contrast, in this embodiment, the junction promoting region 15c is provided between the electron transport material-containing region 15b and the cathode layer 16, and therefore very excellent cell characteristics can be obtained. The reason for this is explained below.
[0021] The absorbance measurement results for the single layer or multilayer films having the following compositions formed on a glass substrate by vacuum deposition are shown in Figure 3. Note that Liq stands for 8-quinolinolatolithium, a compound that corresponds to the above-mentioned bonding-promoting material. [0] Silver (5nm) only [1] β-NBPhen (8 nm) only [2]β-NBPhen(8nm) and Liq(2nm) [3] Lithium (2 nm) and silver (5 nm) [4]β-NBPhen (8 nm) and silver (5 nm) [5]β-NBPhen (8 nm), Liq (2 nm), and Ag (5 nm) For [1] to [5], the absorbance measurement results when the film was heat-treated at 100° C. for 10 minutes in a dry nitrogen atmosphere after deposition are also shown.
[0022] As shown in Figure 3, when β-NBPhen (electron transport material), Liq (bonding promotion material), and silver (metal constituting the cathode layer) were laminated ("5" in Figure 3), optical absorption occurred in the visible light range (500nm to 900nm) that was not observed with either material alone ("0" and "1" in Figure 3). This is thought to be due to the coordination of β-NBPhen to silver, an interaction between β-NBPhen or Liq and silver, or the formation of a charge transfer complex associated with this, or a chemical reaction or interaction involving β-NBPhen, Liq, and silver.
[0023] In addition, when Liq (Li complex) and silver are laminated or when heat treatment is performed after the formation of these, the ligands of the Li complex and silver are bonded, and some of the Li is liberated in a domino effect and diffuses into the layer. As a result, it is possible that the liberated Li and β-NBPhen interact with each other through coordination bonds, etc.
[0024] In the solar cell 10 of this embodiment, it is very important to design the interaction between the electron transport material β-NBPhen or α-NBPhen and other materials to promote the electrical connection between the electron transport layer 15 and the cathode layer 16. As shown in "1" in FIG. 3, the electron transport material β-NBPhen or α-NBPhen is a wide band gap material that does not have a light absorption peak in the visible light region. Therefore, the LUMO position is high in terms of energy level, and it is considered that there is an energy barrier in the electron extraction from the active layer 14 to the cathode layer 16 as it is. In contrast, as in the electron transport layer 15 of this embodiment, by forming the electron transport material-containing region 15b containing the electron transport material and the cathode layer 16 with the connection promotion region 15c containing the connection promotion material, they interact with each other as shown in "5" in FIG. 3. As a result, a level equivalent to a subgap or intra-gap level is generated in the wide band gap of the electron transport layer 15. Alternatively, the dipole moment due to the coordinate bond between the electron transport material and the metal atom acts to reduce the energy barrier in the charge extraction from the active layer 14 to the cathode layer 16, allowing the charge to be smoothly extracted to the outside. As a result, it is believed that good electrical characteristics can be obtained in the solar cell 10 of this embodiment.
[0025] One of the reasons why conventional solar cells using β-NBPhen or α-NBPhen as electron transport materials did not achieve good characteristics is thought to be that the diffusion of metal ions (silver ions in this case) required to create an intra-gap level in the electron transport layer did not occur sufficiently.
[0026] Below, we will explain each layer of the solar cell 10 of this embodiment, and further explain the manufacturing method of the solar cell 10. However, in addition to the layers described below, the solar cell 10 of this embodiment may include any layer or configuration as long as it does not impair the purpose and effect of this embodiment.
[0027] ·Electron transport layer The electron transport layer 15 is a layer for transferring electrons generated in the active layer 14 to the cathode layer 16 and for preventing holes generated in the active layer 14 from moving to the cathode layer 16. As described above, the electron transport layer 15 of this embodiment has, from the active layer 14 side, a fullerene-containing region 15a, an electron transport material-containing region 15b mainly containing α-NBPhen and / or β-NBPhen, and a bond-promoting region 15c containing a bond-promoting material, in this order.
[0028] The fullerene-containing region 15a is 60 The fullerene-containing region 15a may be any region containing fullerene or a derivative thereof. 60 The fullerene or its derivative may be contained in only one kind or in two or more kinds. 60 The fullerene-containing region 15a may contain a material other than fullerene or its derivative (e.g., α-NBPhen and / or β-NBPhen, etc.). In this case, the fullerene-containing region 15a may contain a material other than fullerene or its derivative (e.g., α-NBPhen and / or β-NBPhen, etc.). 60 The fullerene or its derivative is preferably contained at 95 mass % or more, and more preferably at 99 mass % or more. When the electron transport layer 15 contains the fullerene-containing region 15a, the transfer of electrons between the active layer 14 and the electron transport material in the electron transport layer 15 is smoother, and the performance of the solar cell 10 is further improved.
[0029] C 60 Examples of fullerene derivatives include C 60 This includes compounds in which any atom, functional group, or polymer is bonded to fullerene. 60 Examples of atoms, functional groups, and polymers that can be bonded to fullerene include hydrogen atoms, hydroxyl groups, halogen atoms such as fluorine atoms and chlorine atoms, alkyl groups such as methyl groups and ethyl groups, alkenyl groups such as vinyl groups, cyano groups, alkoxy groups such as methoxy groups and ethoxy groups, aromatic hydrocarbon groups such as phenyl groups and naphthyl groups, aromatic heterocyclic groups such as thienyl groups and pyridyl groups, and various polymers. These atoms and functional groups are C 60 Two or more functional groups may be bonded to the fullerene, and the functional groups may form a ring. 60Specific examples of fullerene derivatives include [6,6]-phenyl C 61 This includes butyric acid methyl ester (hereinafter also referred to as "PCBM").
[0030] In the electron transport layer 15 of this embodiment, the thickness of the fullerene-containing region 15a is preferably 1 nm or more and 300 nm or less, and more preferably 10 nm or more and 100 nm or less. When the thickness of the fullerene-containing region 15a is in this range, the performance of the solar cell 10 tends to be further improved.
[0031] On the other hand, the electron transport material-containing region 15b may be a region containing either one or both of α-NBPhen and β-NBPhen. The electron transport material-containing region 15b may contain a component other than α-NBPhen and β-NBPhen in part, but it is preferable that the electron transport material-containing region 15b is mainly composed of α-NBPhen and / or β-NBPhen. Specifically, it is preferable that the electron transport material-containing region 15b contains α-NBPhen and β-NBPhen in an amount of 90% by mass or more, and more preferably 99% by mass or more, based on the total mass of the electron transport material-containing region 15b. The thickness of the electron transport material-containing region 15b is preferably 0.1 nm or more and 100 nm or less, and more preferably 3 nm or more and 30 nm or less. When the thickness of the electron transport material-containing region 15b is within this range, the efficiency of electron transfer from the active layer 14 to the cathode layer 16 tends to be further improved.
[0032] The bond-promoting region 15c is a region containing one or more bond-promoting materials selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum. The bond-promoting region 15c may contain only one type of bond-promoting material, or may contain two or more types of bond-promoting materials. The bond-promoting region 15c may contain α-NBPhen and / or β-NBPhen, or a material constituting the cathode layer 16 described below, in addition to the bond-promoting materials. However, it is preferable that the bond-promoting material is contained in an amount of 1 mass % or more with respect to the total mass of the bond-promoting region 15c.
[0033] The thickness of the bond-promoting region is preferably 0.1 nm to 30 nm, more preferably 1 nm to 10 nm. When the thickness of the bond-promoting region 15c is in this range, the bond-promoting material can further promote the electrical bond between the electron transport layer 15 and the cathode layer 16.
[0034] The total thickness of the electron transport layer 15 is preferably 1 nm or more and 1 μm or less, and more preferably 10 nm or more and 100 nm or less.
[0035] ·Active layer The active layer 14 is a layer containing a metal halide perovskite organic compound (perovskite compound). The perovskite compound has the general formula AB m X n It is a compound with an orthorhombic crystal structure represented by the formula: A is an organic group MA (methylammonium (CH3NH3 + )), organic group FA (formamidinium (HC(NH2)2 + )), or the cesium cation (Cs + ) In addition, B in the general formula represents the metal ion Pb 2+ Or Sn 2+ Furthermore, X in the general formula represents a halogen ion F - , Cl - , I - , or Br -In addition, m is 0.8 to 1.2, and n is 2.8 to 3.2.
[0036] The thickness of the active layer 14 is preferably 50 nm to 2 μm, more preferably 100 nm to 1 μm. When the thickness of the active layer 14 is in this range, it is possible to efficiently absorb sunlight and generate a higher electromotive force.
[0037] Cathode layer The cathode layer 16 may be any layer containing a metal and having high electrical conductivity. The cathode layer 16 may be composed of only one layer, or may be composed of multiple layers. Examples of the metal contained in the cathode layer 16 include silver, gold, copper, aluminum, palladium, indium, tin, zinc, gallium, and the like. The cathode layer 16 may be composed of a single metal such as silver, gold, copper, or aluminum, or may be composed of an alloy such as a silver-palladium-copper alloy. Furthermore, the cathode layer 16 may be composed of a conductive metal oxide such as indium tin oxide, indium zinc oxide, indium gallium oxide, or aluminum-doped zinc oxide. The cathode layer 16 may contain only one of these materials, or may contain two or more of them. Among these, silver is preferable from the viewpoint of easy interaction with the bond-promoting material and the electron transport material in the electron transport layer 15, and further from the viewpoint of high electrical conductivity.
[0038] The thickness of the cathode layer 16 is not particularly limited as long as it can exhibit sufficient conductivity, and is preferably 10 nm or more and 100 μm or less, and more preferably 20 nm or more and 10 μm or less.
[0039] Hole transport layer The hole transport layer 13 is a layer for transferring holes generated in the active layer 14 to the anode 12 and suppressing the movement of electrons generated in the active layer 14 to the anode 12. The hole transport layer 13 may be any layer containing a hole transport material, and examples of the hole transport material include hole transport polymers such as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly[(9,9-dictylfluorenyl-2,7-diyl)-co-(4,4'(N-(4-sec-butylphenyl)diphenylamine)) (TFB), and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS), conjugated polymer materials, conductive polymer materials, and the like.
[0040] Examples of materials for the hole transport layer also include self-assembled monolayer materials having hole selectivity, examples of which include [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (MeO-2PACz), [2-(3,6-dimethoxy-9H-carbazol-9-yl)butyl]phosphonic acid (MeO-4PACz), [2-(9H-carbazol-9-yl)ethyl]phosphonic acid (2PACz), [2 [2-(3,6-dibromo-9H-carbazol-9-yl)ethyl]phosphonic acid (Br-2PACz), [2-(3,6-dimethyl-9H-carbazol-9-yl)ethyl]phosphonic acid (Me-2PACz), [4-(9H-carbazol-9-yl)butyl]phosphonic acid (4PACz) and [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz), etc. The hole transport layer may contain only one type of hole transport material or may contain two or more types.
[0041] The thickness of the hole transport layer is not particularly limited as long as it can exhibit the above-mentioned hole transport performance, and is preferably 1 μm or less, more preferably 100 nm or less.
[0042] ·anode In the solar cell 10 of this embodiment, the anode 12 is disposed on the light-receiving surface side, and therefore the anode 12 is made of a material that is transparent to sunlight. Examples of such anode materials include conductive metal oxides such as indium tin oxide, indium zinc oxide, indium gallium oxide, and aluminum-doped zinc oxide. The anode 12 may contain only one of these materials, or may contain two or more of them.
[0043] The thickness of the anode 12 is not particularly limited as long as it can exhibit sufficient conductivity, and is preferably 10 nm or more and 10 μm or less, and more preferably 100 nm or more and 1 μm or less.
[0044] Transparent substrate The transparent substrate 11 may be any substrate that is transmissive to sunlight and has a strength sufficient to protect the solar cell 10 from external impacts, etc. The transparent substrate 11 may be a substrate made of a resin film or the like, but is preferably a glass substrate in terms of its strength, sunlight transmissivity, etc.
[0045] The manufacturing method of the solar cell of the present embodiment The above-mentioned solar cell 10 can be manufactured by, for example, the following method, but is not limited to, this method. In the manufacturing method of the solar cell 10, the anode 12 is formed in a desired pattern on the transparent substrate 11 by a known method. The method of forming the anode 12 is not particularly limited, and it may be formed by, for example, various coating methods or a deposition method.
[0046] Next, a hole transport layer 13 containing the hole transport material is formed at a desired position on the anode 12. There is no particular limitation on the method for forming the hole transport layer 13. For example, the hole transport layer 13 can be formed by dispersing or dissolving the hole transport material in a liquid, applying the liquid by a known application method (e.g., spin coating), and then removing the liquid.
[0047] An active layer 14 containing the above-mentioned perovskite compound is further formed on the hole transport layer 13. The method for forming the active layer 14 is not particularly limited, but an example of the method is to apply a composition in which the perovskite compound is dispersed or dissolved in a liquid by a spin coating method, and then apply a poor solvent by a spin coating method to crystallize the perovskite compound.
[0048] The fullerene-containing region 15a of the electron transport layer 15 is formed on the active layer 14. The method for forming the fullerene-containing region 15a is not particularly limited. For example, the fullerene-containing region 15a may be formed by a deposition method or the like. 60 The fullerene or a derivative thereof may be dispersed or dissolved in a liquid, and the composition may be applied by a known method (for example, spin coating method, etc.) and then solidified.
[0049] Furthermore, an electron transport material-containing region 15b containing α-NBPhen and / or β-NBPhen is formed on the fullerene-containing region 15a. The method for forming the electron transport material-containing region 15b is not particularly limited, and may be performed by a deposition method or the like. Alternatively, α-NBPhen or β-NBPhen may be dispersed or dissolved in a liquid, which may be applied by a known method (e.g., spin coating), and then solidified.
[0050] Next, the bond-promoting region 15c is formed on the electron transport material-containing region 15b. The method for forming the bond-promoting region 15c is appropriately selected depending on the type of the bond-promoting material. For example, the bond-promoting region 15c may be formed by a deposition method or the like. Alternatively, the bond-promoting material may be dispersed or dissolved in a solvent, applied by a known method (such as a spin coating method), and then solidified.
[0051] Thereafter, the cathode layer 16 is formed on the electron transport layer 15. The cathode layer 16 can be formed by a known method, for example, a vapor deposition method.
[0052] In this embodiment, after the cathode layer 16 is formed, at least the cathode layer 16 and the electron transport layer 15, preferably the entire solar cell 10, are preferably heat-treated. In the absorbance measurement in FIG. 3 described above, when Liq and silver are laminated ("3" in FIG. 3) and further heat-treated, a significant shift in the absorbance peak was observed before and after the heat treatment. In FIG. 3, these peak positions are marked. In other words, it is considered that chemical reactions and physical changes (e.g., formation of a microstructure, etc.) occur due to the lamination of Liq and silver, and these are promoted or further changed by the heat treatment. Therefore, it is considered that the electrical connection between the electron transport layer 15 and the cathode layer 16 is further promoted by the heating, and the electrical characteristics of the solar cell 10 are further improved.
[0053] The heating temperature after the cathode formation is preferably 60°C or higher and 300°C or lower, more preferably 80°C or higher and 180°C or lower. The heating time is preferably 10 seconds to 1 hour, more preferably 1 minute to 20 minutes. If the heating temperature is 300°C or lower, it is unlikely to affect each layer in the solar cell 10. On the other hand, heating at 60°C or higher makes it easier to further promote electrical bonding between the electron transport layer 15 and the cathode layer 16. On the other hand, if the heating time is within the above range, it is easy to obtain a sufficient effect by heating.
[0054] (2) Second aspect The solar cell 10 of the second embodiment is similar to the solar cell 10 of the first embodiment except for the electron transport layer 15. The solar cell 10 also has a structure in which a transparent substrate 11 / anode 12 / hole transport layer 13 / active layer 14 / electron transport layer 15 / cathode layer 16 are laminated in this order. A partially enlarged view of the electron transport layer 15 of this embodiment is shown in FIG. 2B. The electron transport layer 15 of this embodiment is a C-type GaN layer disposed adjacent to the active layer 14. 60 The cathode layer 16 includes a fullerene-containing region 15a containing a fullerene or a derivative thereof, and a bond-promoting region 15d disposed adjacent to the cathode layer 16. The bond-promoting region is a region formed by co-evaporating an electron transport material consisting of α-NBPhen and / or β-NBPhen with a bond-promoting material and / or a metal material.
[0055] The solar cell 10 of this embodiment also has good heat resistance and can be used in high temperature environments because it uses α-NBPhen and / or β-NBPhen as the electron transport material. In this embodiment, the bond-promoting region 15d contains a bond-promoting material and a metal material in addition to the electron transport material, so that very good battery characteristics can be obtained. The reason for this will be explained below.
[0056] As described above, the electron transport material β-NBPhen or α-NBPhen is a wide band gap material that does not have a light absorption peak in the visible light region, and it is considered that there is an energy barrier in the electron extraction from the active layer 14 to the cathode layer 16 as it is. In contrast, in this embodiment, the electron transport material is co-deposited with the bond promotion material and / or metal material. For example, the electron transport material α-NBPhen or β-NBPhen is compatible with the bond promotion material. Therefore, when these are co-deposited, the crystallinity of the electron transport material is reduced, and an amorphous, uniform and highly flat region is formed as the bond promotion region 15d. Then, when the cathode layer 16 is formed on such an electron transport layer 15 (bond promotion region 15d), it is considered that an interaction occurs between the electron transport material and the metal in the cathode layer 16, or an interaction occurs between the electron transport material, the bond promotion material, and the metal in the cathode layer 16. In the junction-promoting region 15d of the electron transport layer 15, a level equivalent to a subgap or intra-gap level is generated in the wide band gap of the electron transport layer 15, or a dipole moment due to a coordinate bond between the electron transport material and the metal material acts, resulting in a reduction in the energy barrier in extracting charges from the active layer 14 to the cathode layer 16, and it is believed that the charges can be smoothly extracted to the outside.
[0057] On the other hand, when an electron transport material and a metal material are co-evaporated, it is believed that the metal material in the electron transport layer 15 (junction promotion region 15d) creates an intra-band level in the electron transport layer, and electrons travel through this level, resulting in good electrical characteristics.
[0058] The following describes the electron transport layer 15 of this embodiment, and further describes a manufacturing method for the solar cell 10. Note that the solar cell 10 of this embodiment may further include any layer or configuration as long as it does not impair the object and effect of this embodiment.
[0059] ·Electron transport layer The electron transport layer 15 of this embodiment is also a layer for transferring electrons generated in the active layer 14 to the cathode layer 16 and for preventing holes generated in the active layer 14 from moving to the cathode layer 16. As described above, the electron transport layer 15 has, from the active layer 14 side, a fullerene-containing region 15a and a bond-promoting region 15d containing α-NBPhen and / or β-NBPhen, and a metal material and / or a bond-promoting material, in this order.
[0060] The material and thickness of the fullerene-containing region 15a are similar to those of the fullerene-containing region 15a of the electron transport layer 15 in the above-mentioned first embodiment.
[0061] On the other hand, the composition of the junction promoting region 15d may be any of the following (i) to (iii). Among these, composition (iii) is particularly preferable because it is easy to improve the performance of the solar cell 10. (i) Combination of an electron transport material and a junction-promoting material (ii) A combination of an electron transport material and a metal material (iii) A combination of an electron transport material, a bond promoting material, and a metal material
[0062] Here, the electron transport material used in the junction promoting region 15d may be either α-NBPhen or β-NBPhen, or both.
[0063] The bond-promoting material that the bond-promoting region 15d may contain is the same as the bond-promoting material used in the bond-promoting region 15c of the first embodiment, and is a compound selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum. The bond-promoting region 15d may contain only one of these, or may contain two or more of them. Among these, 8-quinolinolatolithium is more preferable from the viewpoints of ease of co-deposition with the electron transport material and ease of interaction with the electron transport material and the material constituting the cathode layer 16.
[0064] On the other hand, the metal material that may be contained in the bond-promoting region 15d is preferably a material that is highly conductive and easily co-deposited with the electron transport material, etc. The metal material may be the same as or different from the material (metal) that constitutes the cathode layer 16. Examples of the metal material include silver, gold, copper, aluminum, palladium, indium, tin, zinc, gallium, etc., which may be a single metal or an alloy. Among these, silver is more preferable from the viewpoint of being easily co-deposited with the electron transport material and easily interacting with the electron transport material and the material that constitutes the cathode layer 16.
[0065] When the bond promotion region 15d is a combination of (i) an electron transport material and a bond promotion material, the amount of the bond promotion material relative to the total mass of the bond promotion region 15d is preferably 1 mass% or more and 50 mass% or less, and more preferably 10 mass% or more and 25 mass% or less. When the amount of the bond promotion material is 1 mass% or more, the effect of adding the bond promotion material is more easily obtained. On the other hand, when the amount of the bond promotion material is 50 mass% or less, the amount of the electron transport material (α-NBPhen and / or β-NBPhen) becomes relatively large, and the transfer of electrons from the active layer 14 side to the cathode layer 16 side is easily performed.
[0066] When the bond promotion region 15d is a combination of (ii) an electron transport material and a metal material, the amount of the metal material relative to the total mass of the bond promotion region 15d is preferably 1 mass% to 50 mass%, more preferably 5 mass% to 25 mass%. When the amount of the metal material is 1 mass% or more, the effect of adding the metal material is more easily obtained. On the other hand, when the amount of the metal material is 50 mass% or less, the amount of the electron transport material becomes relatively large, and the transfer of electrons from the active layer 14 side to the cathode layer 16 side is easily performed.
[0067] When the bond promotion region 15d is a combination of (iii) an electron transport material, a bond promotion material, and a metal material, the amount of the bond promotion material relative to the total mass of the bond promotion region 15d is preferably 1% by mass to 25% by mass, more preferably 5% by mass to 25% by mass. The amount of the metal material relative to the total mass of the bond promotion region 15d is preferably 1% by mass to 25% by mass. The total amount of the bond promotion material and the metal material is preferably 2% by mass to 50% by mass, more preferably 5% by mass to 50% by mass. When the amount of the bond promotion material and the metal material is within the above range, it is possible to further promote the electrical bond between the electron transport layer 15 and the cathode layer 16 without impairing the electron transport property of the electron transport material.
[0068] The composition ratio of the electron transport material to the bond promoting material and the metal material in the bond promoting region 15d may be constant or may vary. For example, a gradient may be provided so that the ratio of the metal material increases toward the cathode layer 16.
[0069] The thickness of the bond promotion region 15d is preferably 0.1 nm to 20 nm, more preferably 2 nm to 10 nm. When the thickness of the bond promotion region 15d is within this range, the above-mentioned interaction is likely to occur, and the performance of the solar cell 10 of this embodiment is likely to be further improved.
[0070] The total thickness of the electron transport layer 15 is preferably 1 nm or more and 1 μm or less, and more preferably 10 nm or more and 100 nm or less.
[0071] The manufacturing method of the solar cell of the present embodiment The above-mentioned solar cell 10 can be manufactured, for example, by the following method, but is not limited to this method. In the manufacturing method of the solar cell 10, an anode 12, a hole transport layer 13, and an active layer 14 are formed on a transparent substrate 11 by the method described in the first embodiment.
[0072] Then, the fullerene-containing region 15a of the electron transport layer 15 is formed on the active layer 14. The method for forming the fullerene-containing region 15a is not particularly limited. For example, the fullerene-containing region 15a may be formed by a deposition method or the like. 60 The fullerene or a derivative thereof may be dispersed or dissolved in a liquid, and the composition may be applied by a known method (for example, spin coating method, etc.) and then solidified.
[0073] Furthermore, the electron transport material (α-NBPhen and β-NBPhen) and the metal material and / or the bond-promoting material are co-deposited on the fullerene-containing region 15a to form the bond-promoting region 15d. The co-deposition can be performed by a known method, for example, by using a vacuum deposition apparatus. In addition, the deposition rate is preferably 0.01 nm / sec to 10 nm / sec, more preferably 0.1 nm / sec to 1 nm / sec. The composition in the bond-promoting region 15d may be gradient by gradually changing the film formation conditions.
[0074] Thereafter, the cathode layer 16 is formed on the electron transport layer 15. The cathode layer 16 can be formed by a known method, for example, a vapor deposition method.
[0075] In this embodiment, at least the cathode layer 16 and the electron transport layer 15, preferably the entire solar cell 10, may be heat-treated after the cathode layer 16 is formed. The temperature is preferably 60°C or higher and 300°C or lower, more preferably 80°C or higher and 160°C or lower. The heating time is preferably 1 minute or higher and 1 hour or lower, more preferably 5 minutes or higher and 20 minutes or lower. If the heating temperature is 300°C or lower, it is difficult to affect each layer in the solar cell 10. On the other hand, heating at 60°C or higher makes it easier to further promote electrical bonding between the electron transport layer 15 and the cathode layer 16. On the other hand, if the heating time is within the above range, it is easy to obtain a sufficient effect by heating.
[0076] (3) Third aspect The solar cell 10 of the third embodiment is similar to the solar cell 10 of the first embodiment except for the junction promoting region of the electron transport layer 15. The solar cell 10 also has a structure in which a transparent substrate 11 / anode 12 / hole transport layer 13 / active layer 14 / electron transport layer 15 / cathode layer 16 are laminated in this order. The electron transport layer 15 of this embodiment is a C layer disposed adjacent to the active layer 14 as shown in FIG. 2A. 60 Three regions are arranged in sequence: a fullerene-containing region 15a containing fullerene or its derivative; an electron transport material-containing region 15b containing the electron transport materials α-NBPhen and / or β-NBPhen; and a bond promotion region 15c containing α-NBPhen and / or β-NBPhen and a material constituting the cathode layer 16 (hereinafter also referred to as the "cathode constituent material").
[0077] The solar cell 10 of this embodiment also has good heat resistance and can be used in high temperature environments because it uses α-NBPhen and / or β-NBPhen as the electron transport material. In this embodiment, the bond promotion region 15c contains α-NBPhen and / or β-NBPhen and a cathode constituent material, so that very good battery characteristics can be obtained. The reason for this will be explained below.
[0078] As described above, the electron transport material β-NBPhen or α-NBPhen is a wide band gap material that does not have a light absorption peak in the visible light region, and it is considered that there is an energy barrier in electron extraction from the active layer 14 to the cathode layer 16 as it is. In contrast, in this embodiment, the junction promotion region 15c contains α-NBPhen or β-NBPhen and the above-mentioned cathode constituent material, and it is considered that they interact with each other. In the junction promotion region 15c of such an electron transport layer 15, a level equivalent to a subgap or intra-gap level is generated in the wide band gap of the electron transport layer 15, or a dipole moment due to a coordinate bond between the electron transport material and the cathode constituent material acts, and as a result, it is considered that the energy barrier in charge extraction from the active layer 14 to the cathode layer 16 is reduced, and the charge can be smoothly extracted to the outside.
[0079] The bond-promoting region 15c is formed by stacking an NBPhen layer containing α-NBPhen or β-NBPhen and a metal material layer containing a cathode-constituting material adjacent to each other and heating them, as described later. That is, the bond-promoting region 15c is formed by diffusing the cathode-constituting material from the metal material layer side to the NBPhen layer side. Therefore, the concentration of the cathode-constituting material in the bond-promoting region 15c is usually inclined so that the concentration is high on the cathode layer 16 side and low on the electron transport material-containing region 15b side. The amount of the cathode-constituting material in the entire bond-promoting region 15c is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 25% by mass or less, relative to the mass of the bond-promoting region 15c. When the amount of the cathode-constituting material is 1% by mass or more, the effect of including the cathode-constituting material is more easily obtained. On the other hand, when the amount of the cathode-constituting material is 50% by mass or less, the amount of the electron transporting material is relatively large, and electrons are easily transferred from the active layer 14 side to the cathode layer 16 side.
[0080] The thickness of the bond promotion region 15c is preferably 0.1 nm to 20 nm, more preferably 2 nm to 10 nm. When the thickness of the bond promotion region 15c is within this range, the above-mentioned interaction is likely to occur, and the performance of the solar cell 10 of this embodiment is likely to be further improved.
[0081] The total thickness of the electron transport layer 15 is preferably 1 nm or more and 1 μm or less, and more preferably 10 nm or more and 100 nm or less.
[0082] (Modification) In the above, it has been described that the electron transport layer 15 is composed of three regions, namely, the fullerene-containing region 15a, the electron transport material-containing region 15b, and the junction-promoting region 15c, but the electron transport material-containing region 15b does not necessarily have to be disposed. In other words, the electron transport material-containing region 15b and the junction-promoting region 15c may be integrated, and the cathode constituent material may be contained in the entire region.
[0083] The manufacturing method of the solar cell of the present embodiment The above-mentioned solar cell 10 can be manufactured, for example, by the following method, but is not limited to this method. In the manufacturing method of the solar cell 10, an anode 12, a hole transport layer 13, and an active layer 14 are formed on a transparent substrate 11 by the method described in the first embodiment.
[0084] Then, the fullerene-containing region 15a of the electron transport layer 15 is formed on the active layer 14. The method for forming the fullerene-containing region 15a is not particularly limited. For example, the fullerene-containing region 15a may be formed by a deposition method or the like. 60 The fullerene or a derivative thereof may be dispersed or dissolved in a liquid, and the composition may be applied by a known method (for example, spin coating method, etc.) and then solidified.
[0085] Furthermore, an NBPhen layer containing α-NBPhen and / or β-NBPhen is formed on the fullerene-containing region 15a. The method for forming the NBPhen layer is not particularly limited, and may be performed by a deposition method or the like. Alternatively, α-NBPhen or β-NBPhen may be dispersed or dissolved in a liquid, which may be applied by a known method (e.g., spin coating), and then solidified.
[0086] Next, a metal material layer containing a metal material is formed adjacent to the NBPhen layer. The metal material here is synonymous with the cathode constituent material. The metal material layer can be formed by a known method, for example, by a vapor deposition method.
[0087] Thereafter, the metal material layer and the NBPhen layer are heat-treated. At this time, other layers may be heat-treated at the same time. The heat treatment causes the cathode constituent material in the metal material layer to diffuse to the NBPhen layer side, forming the above-mentioned bond-promoting region 15c. The region where the cathode constituent material has not diffused becomes the above-mentioned electron transport material-containing region 15b. However, as described above, heating may be performed so that the cathode constituent material diffuses throughout the entire NBPhen layer.
[0088] The heating temperature at this time is preferably 60°C or higher and 300°C or lower, and more preferably 80°C or higher and 180°C or lower. The heating time is preferably 10 seconds to 1 hour, and more preferably 1 minute to 20 minutes. If the heating temperature is 300°C or lower, it is unlikely to affect each layer in the solar cell 10. On the other hand, the bonding promotion region 15c is formed by heating to 60°C or higher.
[0089] (4)Other In the above, a solar cell in which sunlight is incident from the anode (transparent electrode) side has been described. However, the solar cell of the present invention may be configured so that sunlight is incident from the cathode layer side. In this case, a transparent electrode such as indium tin oxide is used for the cathode layer. When fabricating a perovskite / silicon tandem solar cell, such a top-light-incident solar cell element structure becomes important. And even in such a top-light-incident solar cell, by forming the above-mentioned junction-promoting region in the electron transport layer, it is possible to maximize the interaction between the electron transport material and the transparent electrode, improve the fill factor, reduce the resistance value, and improve the conversion efficiency, thereby improving initial characteristics.
[0090] In a top-illumination solar cell element structure, forming a layer made of a thin silver film or the like on the light-receiving surface side is likely to deteriorate the cell characteristics. In contrast, when an electron transport material and a metal material are co-deposited as in the junction-promoting region of the second embodiment described above, the transparency is higher than when a thin silver film is formed, and light blocking is reduced. Furthermore, when the junction-promoting region of the electron transport layer contains a material with a high glass transition temperature, such as α-NBPhen or β-NBPhen, as in the second embodiment, the electron transport layer is less likely to be damaged even if a transparent conductive film is formed by sputtering or the like. Furthermore, it is also possible to form a high-quality transparent conductive film by increasing the temperature during film formation.
[0091] (5) Solar cell module The solar cell can be modularized by sealing it with a sealing material or the like. The structure and material of the sealing material for the solar cell are not particularly limited as long as it can protect the solar cell from oxygen, water, etc. Examples of the sealing material include a glass cap, a plastic film with gas barrier properties, an organic thin film or an inorganic thin film with gas barrier properties, or a laminate of these. EXAMPLES
[0092] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited thereto.
[0093] <Material preparation> The following materials and compositions were prepared for forming a solar cell. All were stored in a dry nitrogen environment.
[0094] Hole transport layer forming solution 1: 1 mM solution of [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (MeO-2PACz) (Tokyo Chemical Industry Co., Ltd.) in ethanol (Fujifilm Wako Co., Ltd.) Hole transport layer forming solution 2: 2 mM solution of [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (MeO-2PACz) (Tokyo Chemical Industry Co., Ltd.) in isopropyl alcohol (Fujifilm Wako Co., Ltd.)
[0095] · Active layer forming solution: Perovskite compound solution prepared by the method described below
[0096] Fullerene derivative solution: 20 mg / mL PCBM (Tokyo Chemical Industry Co., Ltd.) in chlorobenzene (Fujifilm Wako Co., Ltd.)
[0097] Antisolvent 1: Anisole Poor solvent 2: Ethyl acetate (Fujifilm Wako Co., Ltd.)
[0098] Evaporation material 1: BCP (TCI) Evaporation material 2: α-NBPhen (manufactured by Chemipro Chemicals) Evaporation material 3: β-NBPhen (manufactured by Chemipro Chemicals) Lithium metal complex: 8-quinolinolatrium (Liq) (manufactured by Chemipro Chemicals)
[0099] (Method for preparing a perovskite compound solution) Formamidine hydroiodide (FAI), lead(II) iodide (PbI2), methylammonium bromide (MABr), lead bromide (PbBr2) (all manufactured by Tokyo Chemical Industry Co., Ltd.), and cesium iodide (CsI) (manufactured by Sigma-Aldrich) were dissolved in a mixed solution of N,N-dimethylformamide (DMF) (manufactured by Fuji Film Wako Co., Ltd.) and dimethyl sulfoxide (DMSO) (manufactured by Fuji Film Wako Co., Ltd.) in a volume ratio of 1:4. Then, a perovskite compound (Cs 0.05 (FA 0.76 MA 0.24 ) 0.95 Pb(I 0.76 / Br 0.24 ) 3) A solution was prepared.
[0100] 1. First Aspect [Example 1-1] A solar cell was fabricated by the following method. Figures 4A to 4F show a process chart, and Figure 5 shows an exploded perspective view of the fabricated solar cell.
[0101] Preparation of a substrate with an anode (transparent electrode) A transparent substrate (glass substrate) 11 (20 mm×25 mm×0.65 mm) on which a transparent electrode 12 (indium tin oxide (ITO)) was formed in the pattern shown in FIG. 5 was prepared (FIG. 4A). The glass substrate with the transparent electrode was immersed in an aqueous surfactant solution, water, acetone, and 2-propanol in that order, and ultrasonically cleaned for 30 minutes each. After cleaning, the substrate was dried at 60° C. for 16 hours, and the surface was modified in an ultraviolet-ozone surface modification device for 30 minutes. Then, the other areas were covered with masking tape (heat-resistant and solvent-resistant tape, not shown) except for the area where the hole transport layer 13 was to be formed, and the substrate was immediately transported to a dry nitrogen environment.
[0102] Formation of hole transport layer 4B, the hole transport layer forming solution 1 for forming a self-assembled monolayer was applied by a spin coater onto the transparent electrode 12 of the above-mentioned glass substrate with a transparent electrode. Then, a heat treatment was performed at 100° C. for 10 minutes to obtain a hole transport layer 13.
[0103] Formation of the active layer As shown in FIG. 4C, the above-mentioned perovskite compound solution was dropped onto the entire surface of the glass substrate with the transparent electrode on which the hole transport layer 13 was formed, and anisole was dropped as a poor solvent at an appropriate timing. This caused the perovskite compound in the perovskite compound solution to start crystallizing. After that, the active layer (perovskite layer) 14 was obtained by heat treatment at 100° C. for 10 minutes.
[0104] Formation of electron transport layer As shown in FIG. 4D, the fullerene derivative solution (PCBM-containing solution) was spin-coated on the entire surface of the glass substrate with transparent electrodes on which the active layer 14 was formed, and dried at room temperature to form a fullerene-containing region. Then, β-NBPhen was deposited by vacuum thermal evaporation to a thickness of 8 nm in an area of 10 mm×15 mm to form an electron transport material-containing region. Furthermore, 8-quinolinolatolithium (Liq) was deposited to a thickness of 2 nm to form a bond-promoting region. Note that, although FIG. 4D shows the electron transport layer 15 formed on the entire surface of the glass substrate with transparent electrodes, in this embodiment, the electron transport material-containing region and bond-promoting region of the electron transport layer 15 are formed on a pattern as shown in the exploded view of FIG. 5.
[0105] Cathode layer formation The masking tape was peeled off, and unnecessary portions of the hole transport layer 13, active layer 14, and electron transport layer 15 were removed as shown in FIG. 4E, to expose the transparent electrode 12 at a desired position. Furthermore, as shown in FIG. 4F, silver was vacuum-deposited on the bond-promoting region of the electron transport layer 15 to form a cathode layer 16. Then, a heat treatment was performed at 100° C. for 10 minutes in a dry nitrogen environment. At the same time as forming the cathode layer 16, a silver electrode was also formed on a part of the transparent electrode 12 (the region indicated by 12a in FIG. 5) to reduce contact resistance.
[0106] Characteristics measurement In the solar cell 10 fabricated as described above, the hole transport layer 13, the active layer 14, and the electron transport layer 15 have almost no electrical conduction in the surface direction. Therefore, only the rectangular region (3 mm x 3 mm) where all these layers overlap is effective as a solar cell. In addition, the region that does not include both the cathode layer 16 and the transparent electrode 11 does not substantially contribute to power generation and does not hinder power generation. For example, as shown in the exploded view of FIG. 5, the transparent electrode 12 is divided into three regions, and only the central region contributes to power generation. The two regions on both sides are isolated, and the cathode layer is drawn out to these regions to prevent the measurement probe from penetrating the active layer 14. In addition, in the solar cell, a part of the transparent electrode (anode) 12 is exposed, making it possible to measure the characteristics. In addition, a silver electrode is formed on the exposed part of the transparent electrode 12 (the region represented by 12a) to reduce contact resistance.
[0107] Although the solar cell is a perovskite type, it is stable in the atmosphere for a time longer than the time required for measurement. Therefore, the current probe and voltage probe for measurement were placed in contact with the positions shown in FIG. 5, and artificial sunlight was irradiated from the glass substrate 11 side to measure the current-voltage characteristics during power generation using the four-terminal method. The results are shown in the graph at the bottom right of FIG. 6. In FIG. 6, the forward sweep (when the voltage rises) is shown by a solid line, and the reverse sweep (when the voltage falls) is shown by a dotted line when the voltage was swept from 0V to 1.25V over 62.5 seconds.
[0108] [Comparative Example 1-1] A solar cell was fabricated in the same manner as in Example 1-1, except that bathocuproine (BCP) was used instead of β-NBPhen when forming the electron transport material-containing region of the electron transport layer 15, and the junction promotion region was not formed. The current-voltage characteristics of the solar cell are shown in the graph at the top left of FIG.
[0109] [Comparative Example 1-2] A solar cell was produced in the same manner as in Example 1-1, except that no electron transport material-containing region was formed in the electron transport layer 15. The current-voltage characteristics of the solar cell are shown in the graph in the upper right corner of FIG.
[0110] [Comparative Example 1-3] A solar cell was fabricated in the same manner as in Example 1-1, except that no junction promotion region was formed in the electron transport layer 15. The current-voltage characteristics of the solar cell are shown in the graph at the bottom left of FIG.
[0111] [Consideration 1] As shown in each graph of FIG. 6, in Comparative Example 1-2 in which the electron transport layer 15 does not have an electron transport material-containing region and Comparative Example 1-3 in which the electron transport layer 15 does not have a junction-promoting region, the slope of the current-voltage curve near the open circuit voltage was small and the series resistance was large compared to Comparative Example 1-1 in which BCP was used as the electron transport material. In other words, the fill factor was low and the power generation efficiency was low. The "fill factor" is the amount obtained by dividing the energy conversion efficiency by the product of the short-circuit current and the open circuit voltage, and is the amount that increases as the series resistance is small and there is no leakage current.
[0112] In contrast, in Example 1-1, in which the electron transport layer 15 has a fullerene-containing region, an electron transport material-containing region, and a junction-promoting region, the series resistance and fill factor were equivalent to those of Comparative Example 1-1, in which BCP was used as the electron transport material. In other words, when β-NBPhen was used as the electron transport material, the fill factor became equivalent to that of the case in which BCP was used as the electron transport material (Comparative Example 1-1) only after the junction-promoting region was formed. This result suggests that the junction-promoting region contributed to the electrical contact between the electron transport layer and the cathode layer (Ag layer).
[0113] [Comparative Example 1-4] A solar cell was fabricated in the same manner as in Comparative Example 1-3, except that the electron transport material was changed from β-NBPhen to α-NBPhen. In other words, Comparative Example 1-4 has a fullerene-containing region and an electron transport material-containing region, but does not have a junction-promoting region. The current-voltage characteristics during power generation of the solar cell were also measured by the four-terminal method. The results are shown in FIG. 7.
[0114] In addition, FIG. 7 shows not only the results of Comparative Example 1-4, but also the results of the above-mentioned Examples 1-1, Comparative Examples 1-1, 1-2, and 1-3. In addition, FIG. 7 shows the results (energy conversion efficiency, open circuit voltage, short circuit current density, and fill factor) of forward and reverse sweeps for four samples each for the cases where heat treatment (heat treatment at 100°C for 10 minutes) was performed and not performed after the production of the solar cell of each Example and Comparative Example. In addition, the cases where β-NBPhen or α-NBPhen was heated correspond to the Examples (the above-mentioned third embodiment), so these are referred to as Examples 1-2 and 1-3. Actual data is also shown in Table 1 below.
[0115] [Table 1]
[0116] [Consideration 2] As shown in FIG. 7 and Table 1, although there was variation for each sample, the conversion efficiency and electrical characteristics were good in Example 1-1 (the first and second data from the right in each graph in FIG. 7) in which a fullerene-containing region, an electron transport material-containing region, and a junction-promoting region were formed in the electron transport layer 15. When BCP was used as the electron transport material (Comparative Example 1-1, the first and second data from the left in each graph in FIG. 7), the heat resistance was insufficient, so the conversion efficiency was significantly reduced by heat treatment. Similarly, when the electron transport layer did not have an electron transport material-containing region (Comparative Example 1-2, the third and fourth data from the left in each graph in FIG. 7), the conversion efficiency was also significantly reduced by heat treatment. Furthermore, when the electron transport layer did not have a junction-promoting region (Liq) and was not heated (Comparative Example 1-3 and Comparative Example 1-4, the fifth and seventh data from the left in each graph in FIG. 7), the results were worse than when BCP was used as the electron transport material. On the other hand, when these were heated (Examples 1-2 and 1-3, the sixth and eighth data from the left in each graph of FIG. 7), a bonding-promoting region was formed and good results were obtained. However, Example 1-1 (with heating), which provided a bonding-promoting region containing Liq, gave better results.
[0117] 2. Second Aspect [Reference example NBP] Preparation of a substrate with an anode A transparent substrate (glass substrate) on which 2 mm-wide striped transparent electrodes (indium tin oxide (ITO)) were formed was ultrasonically cleaned in a surfactant aqueous solution, water, acetone, and 2-propanol, in that order, for 30 minutes each, and then dried at 60°C for 16 hours. After that, the surface was treated for 30 minutes using an ultraviolet-ozone surface modification device.
[0118] Formation of hole transport layer The above-mentioned solution 2 for forming a hole transport layer was dropped onto the transparent electrode of the above-mentioned glass substrate with a transparent electrode, and a film was formed by spin coating at 3000 rpm for 30 seconds, and then heated on a hot plate at 100°C for 10 minutes to form a hole transport layer.
[0119] Formation of the active layer After 0.1 mL of the above-mentioned perovskite compound solution was dropped onto the hole transport layer, the substrate was spin-coated at 5000 rpm for 35 seconds. During the spin-coating, 10 seconds after the start of spinning, 0.3 mL of ethyl acetate was dropped onto the rotating substrate as a poor solvent. After the spin-coating was completed, the substrate was transferred to a hot plate and heated at 100°C for 30 minutes in a nitrogen atmosphere to obtain a dark brown active layer (perovskite layer).
[0120] ·Electron transport layer The above-mentioned fullerene derivative solution (PCBM solution) was spin-coated on the active layer so that the thickness of the fullerene-containing region was 40 nm. After that, the parts of the fullerene-containing region of the hole transport layer 13, the active layer 14, and the electron transport layer 15 formed on the glass substrate with the transparent electrode that were not required for power generation were scraped off with a cotton swab or the like in a glove box to expose the peripheral anode (ITO) surface. Next, the substrate was placed in a vacuum deposition apparatus, and only β-NBPhen was vacuum deposited under high vacuum while adjusting the deposition rate to be between approximately 0.1 nm / sec and 0.2 nm / sec, to form an electron transport material-containing region.
[0121] Cathode layer formation A metal mask with 2 mm stripes was set in the vacuum deposition apparatus so as to be perpendicular to the stripes of the transparent electrode. Then, under high vacuum, the deposition rate was adjusted to about 0.1 nm / sec to 0.6 nm / sec to form a cathode layer (silver layer) with a thickness of 70 nm, thereby obtaining a solar cell.
[0122] The solar cell is made up of an anode layer (ITO: 130 nm) / hole transport layer (MeO-2PACz: 1 nm) / active layer (Cs 0.05 (FA 0.76 MA 0.24 ) 0.95 Pb(I 0.76 Br 0.24 )3: 380 nm) / electron transport layer (PCBM: 40 nm / β-NBPhen: 8 nm) / cathode layer (Ag: 70 nm).
[0123] · Bonding of sealing materials The solar cell fabricated as described above was pulled out into a glove box linked to a vacuum deposition apparatus, and was covered with a separately prepared glass cap with a recess to seal it. At this time, the glass cap was attached to the solar cell by ultraviolet curing resin. The joint surface between the glass cap and the solar cell was adjusted to be outside the power generation area of the solar cell and inside the outer periphery of the solar cell. The characteristics of the solar cell were measured using the electrode part located on the outside of the glass cap. In addition, in order to prevent deterioration of the metal electrode due to oxidation in the atmosphere, a transparent electrode-attached substrate was used in which a transparent electrode (anode) and another ITO pad electrode, which serves as an extraction electrode on the cathode side, were patterned in advance at a position electrically separated from the transparent electrode. More specifically, a transparent electrode-attached glass substrate was used in which both the ITO stripe electrode on the anode side and the ITO pad electrode on the cathode side were exposed to the outside of the glass cap after sealing with the glass cap.
[0124] In this reference example, the perovskite layer is formed by spin coating at a high speed of 5000 rpm, so the thickness of the perovskite layer is thinner than the active layer thickness of a normal solar cell, which is 550 nm to 650 nm, the area of one cell is 2 mm × 2 mm, the solvent used in forming the hole transport layer is different from that in the above-mentioned Example 1, and the solar cell characteristics are evaluated using measurements by a two-terminal method, which are different from those in the above-mentioned Example 1. Therefore, although a completely identical characteristic comparison with the above-mentioned first embodiment is not possible, a relative evaluation within the examples of the second embodiment performed under the same fabrication conditions is possible.
[0125] [Reference example BCP] A solar cell was produced in the same manner as in Reference Example NBP, except that bathocuproine (BCP) was used instead of β-NBPhen as the electron transport material of the electron transport layer, and the solar cell was sealed with a glass cap and modularized in the same manner as above.
[0126] [evaluation] The characteristics of each solar cell module are shown in Table 2 below. To see the change in element characteristics due to heating, the average value of the characteristics of 15 elements was calculated. In addition, the characteristics of the solar cell module after fabrication (without heat treatment) and the solar cell module after heat treatment at 100°C for 10 minutes were evaluated. In the embodiment in which Reference Example NBP was heated, a bond promotion region was formed between the electron transport layer and the cathode layer, and therefore this is designated as Example 1-3. [Table 2]
[0127] [Consideration] The above simply compares the performance of solar cell modules using β-NBPhen as the electron transport material and BCP as the electron transport material. Comparing these, the initial characteristics before heat treatment were better for solar cell modules using BCP than for those using β-NBPhen. However, after heat treatment, the characteristics of the solar cell module using BCP decreased in all aspects, including short circuit current density, open circuit voltage, fill factor, and conversion efficiency. Even in the verification of one element that showed the top data, the open circuit voltage and fill factor decreased significantly after heat treatment, and the conversion efficiency decreased by about 1.5%.
[0128] On the other hand, the characteristics of the element using β-NBPhen after heat treatment (Example 1-3) showed a slight decrease in short-circuit current density and open-circuit voltage on average, but an improvement in fill factor, resulting in an increase in conversion efficiency, and showed higher characteristics than the case using BCP. In the verification of one element showing the top data, after heat treatment, the short-circuit current density was almost unchanged, the open-circuit voltage was decreased by about 0.02 V, the fill factor was improved by about 2%, and the conversion efficiency was improved by about 0.1%.
[0129] In addition, to observe the change in film quality due to heating of each of the electron transport layers, a 40 nm PCBM film was formed on an ITO substrate by spin coating, and then two types of electron transport materials (β-NBPhen and BCP) were formed into 40 nm films by vacuum deposition to create laminated films. The two samples were heated at 100°C for 1 hour in a nitrogen atmosphere, and the surface of the laminated film after heating was observed with an AFM and optical microscope. As a result, the film laminated with BCP became cloudy after heating, and large aggregates and crystals of organic matter, as well as voids, were observed. On the other hand, no aggregates of organic matter were observed in the sample formed with β-NBPhen. The transparency of the film was maintained unchanged from before the heat treatment, and a uniform film surface was confirmed.
[0130] [Examples 2-1a, 2-1b, and 2-1c] Solar cell modules were fabricated in the same manner as in the above-mentioned Reference Example NBP, except that the following junction promoting region was formed instead of the electron transport material-containing region of the electron transport layer of the above-mentioned Reference Example NBP.
[0131] Formation of junction-promoting regions β-NBPhen and Liq were co-deposited on the fullerene-containing region (PCBM) of the electron transport layer. The deposition conditions were adjusted so that the mixing ratio of β-NBPhen to Liq was 10 mass% (Example 2-1a), 20 mass% (Example 2-1b), or 30 mass% (Example 2-1c).
[0132] [Comparative Examples 2-1a, 2-1b, and 2-1c] Solar cell modules were fabricated in the same manner as in the above-mentioned Reference Example NBP, except that the following comparative junction-promoting region was formed instead of the electron transport material-containing region of the electron transport layer of the above-mentioned Reference Example NBP.
[0133] Formation of comparative junction-promoting regions BCP and Liq were co-deposited on the fullerene-containing region (PCBM) of the electron transport layer. The deposition conditions were adjusted so that the mixture ratio of BCP and Liq was 10 mass% (Comparative Example 2-1a), 20 mass% (Comparative Example 2-1b), or 30 mass% (Comparative Example 2-1c) of Liq to β-NBPhen.
[0134] [evaluation] The conversion efficiency of each solar cell module of the examples and comparative examples was measured in the same manner as described above. For examples 2-1a, 2-1b, and 2-1c, the above-mentioned reference example NBP was used as a reference, and for comparative examples 2-1a, 2-1b, and 2-1c, the above-mentioned reference example BCP was used as a reference.
[0135] [Table 3]
[0136] [Consideration] As shown in Table 3, in Comparative Examples 2-1a, 2-1b, and 2-1c having a comparative junction-promoting region in which BCP and Liq were co-deposited, the conversion efficiency was lower than that of Reference Example BCP in which only BCP was deposited. In addition, although not shown in Table 3, the open circuit voltage was also lower. Furthermore, the conversion efficiency after heating was further reduced.
[0137] On the other hand, in Examples 2-1a and 2-1b in which the electron transport layer had a junction-promoting region in which β-NBphen and Liq were co-deposited, the decrease in conversion efficiency was smaller than that of Reference Example NBP in which only β-NBphen was deposited. Furthermore, the degree of decrease after heating was smaller than that of Comparative Examples 2-1a, 2-1b, and 2-1c, although not shown in Table 3.
[0138] [Example 2-2] Solar cell modules were fabricated in the same manner as in the above-mentioned Reference Example NBP, except that the following junction promoting region was formed instead of the electron transport material-containing region of the electron transport layer of the above-mentioned Reference Example NBP.
[0139] Formation of junction-promoting regions On the fullerene-containing region of the electron transport layer, β-NBPhen and silver were co-deposited to form a junction-promoting region. The mixture ratio of β-NBPhen and silver was adjusted so that the ratio of silver to the deposition rate of β-NBPhen was 8 mass % while referring to the value of the film thickness monitor.
[0140] [Comparative Example 2-2] A solar cell module was obtained in the same manner as in Example 2-2, except that bathocuproine (BCP) was used instead of β-NBPhen when forming the junction-promoting region. That is, a comparative junction-promoting region (8 nm) consisting of BCP and silver was formed. The mixture ratio of BCP and silver was adjusted so that the ratio of silver to the deposition rate of BCP was 8 mass % while referring to the value of the film thickness monitor.
[0141] [evaluation] The conversion efficiency of each solar cell module of Example 2-2 and Comparative Example 2-2 was measured in the same manner as described above. For Example 2-2, the above-mentioned Reference Example NBP was used as a reference, and for Comparative Example 2-2, the above-mentioned Reference Example BCP was used as a reference. The results are shown in Table 4.
[0142] [Table 4]
[0143] [Consideration] As shown in Table 4, when the electron transport layer had a comparative junction-promoting region in which BCP and silver were vapor-deposited (Comparative Example 2-2), the open-circuit voltage was reduced by 0.04 V, but the fill factor was improved by 2%, and the conversion efficiency was almost the same, compared to the reference example BCP in which only BCP was vapor-deposited. However, when the solar cell module was heated, the characteristics were significantly reduced.
[0144] On the other hand, when the electron transport layer had a junction promoting region in which β-NBPhen and silver were co-deposited (Example 2-2), the open circuit voltage was reduced by 0.02 V, but the fill factor was improved by 4%, and the conversion efficiency was improved by 0.6%, compared to Reference Example NBP in which only β-NBPhen was deposited. Furthermore, even when the solar cell module was heated, almost no deterioration in characteristics was observed.
[0145] [Example 2-3] A solar cell module was obtained in the same manner as in Example 2-1a, except that β-NBPhen, Liq (10 mass%), and Ag (8 mass%) were co-deposited when forming the junction-promoting region (8 nm) of the electron transport layer. The mixing ratio of β-NBPhen, Liq, and Ag was adjusted by referring to the value of the film thickness monitor so that the ratio of Liq and the ratio of Ag to the deposition rate of BCP were as described above.
[0146] [evaluation] The performance of the solar cell module (junction promotion region: β-NBPhen+Liq+Ag) produced in Example 2-3 was compared with that of the solar cell module (junction promotion region: β-NBPhen+Liq) produced in the above-mentioned Example 2-1a.
[0147] As a result, in the solar cell module of Example 2-1a, when the heat treatment was performed, the fill factor after the heat treatment was improved and the conversion efficiency increased by 0.2% compared to before the heat treatment. On the other hand, the solar cell module of Example 2-3 had a fill factor about 4% higher than that of Example 2-1a, and the change after heat treatment was small. Therefore, overall, the configuration of Example 2-3 had high initial characteristics and little change in characteristics before and after heat treatment among the elements using β-NBPhen in the electron transport layer. This is thought to be because the amorphous nature of β-NBPhen was improved by the co-deposition of Liq, and the co-deposition of silver promoted the interaction between β-NBPhen and silver, improving the electrical connection at the interface.
[0148] 3. Top-illuminated perovskite solar cell module [Comparative Example 3-1] Each layer was formed in the same manner as in the above-mentioned Reference Example BCP, and a top-illumination type perovskite solar cell was fabricated. In this solar cell module, C was used instead of PCBM when forming the fullerene-containing region of the electron transport layer. 60 The metal material of the cathode layer was changed from silver to ITO (deposited using a sputtering device). The solar cell element structure is as follows: anode: ITO (20 nm) / hole transport layer: MeO-2PACz (1 nm) / active layer: Cs 0.05 (FA 0.76 MA 0.24 ) 0.95 Pb(I 0.76 Br 0.24 )3(380nm) / electron transport layer:{C 60 (30 nm) / BCP (8 nm)} / cathode layer: ITO (100 nm).
[0149] [Comparative Example 3-2] The electron transport layer is 60 A solar cell module was produced in the same manner as in Comparative Example 3-1, except that the deposition was co-deposition (8 nm) of BCP (30 nm) / BCP+Ag (Ag: 8 mass %).
[0150] [Comparative Example 3-3] The electron transport layer is 60 A solar cell module was fabricated in the same manner as in Comparative Example 3-1, except that the composition was (30 nm) / BCP(8 nm) / Ag(8 nm).
[0151] [Example 3] The electron transport layer is 60 A solar cell module was produced in the same manner as in Comparative Example 3-1, except that the layer was co-evaporated (8 nm) by using β-NBPhen+Liq (5 mass %)+Ag (8 mass %).
[0152] [evaluation] The fill factor and conversion efficiency were measured in the same manner as described above for the solar cells of Comparative Examples 3-1, 3-2, and 3-3 and Example 3. The results are shown in Table 5. [Table 5]
[0153] [Consideration] As shown above, the conversion efficiency was improved with the improvement of the fill factor when a co-evaporated film (8 nm) of BCP and silver was used (Comparative Example 3-2) compared to when only BCP was used in the (comparative) junction-promoting region of the electron transport layer (Comparative Example 3-1).
[0154] On the other hand, when a thin silver film was inserted instead of the co-evaporated film of BCP and silver (Comparative Example 3-3), the fill factor improved to 62%, but the 8-nm-thick silver film blocked the light, reducing the amount of light entering the active layer by about half, and the current value was halved, resulting in a low conversion efficiency.
[0155] In addition, in the solar cell module using β-NBPhen as the electron transport material in Example 3, the characteristics were improved compared to the element using BCP, and a conversion efficiency of 11.0% was obtained. It is believed that the efficiency of this element can be further improved by optimizing the structure. [Industrial Applicability]
[0156] According to the present invention, a perovskite solar cell having excellent power generation characteristics and high heat resistance, and a solar cell module using the same can be obtained. The solar cell and solar cell can be easily manufactured and can be used for various purposes. [Explanation of symbols]
[0157] 10 Solar Cell 11 Transparent substrate 12 Anode 13 Hole transport layer 14 Active layer 15 Electron transport layer 15a Fullerene-containing region 15b Region containing electron transport material 15c, 15d Bonding promotion region 16 Cathode
Claims
1. an active layer including a metal halide perovskite compound; an electron transport layer disposed on the active layer; a cathode layer disposed adjacent to the electron transport layer; A solar cell having the electron transport layer contains 9-bis(naphthalene-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalene-2-yl)-4,7-diphenyl-1,10-phenanthroline, and has a bonding promotion region in a region adjacent to the cathode layer for promoting electrical bonding with the cathode layer; Solar cell.
2. the adhesion-promoting region comprises one or more adhesion-promoting materials selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum; The solar cell according to claim 1 .
3. the electron transport layer further has an electron transport material-containing region containing the 9-bis(naphthalene-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalene-2-yl)-4,7-diphenyl-1,10-phenanthroline on the active layer side of the junction promoting region; The solar cell according to claim 2 .
4. The electron transport layer is provided with a region closer to the active layer than the region containing the electron transport material, 60 Further comprising a fullerene-containing region comprising a fullerene or a derivative thereof. The solar cell according to claim 3 .
5. The conjugation-promoting region is the 9-bis(naphthalen-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalen-2-yl)-4,7-diphenyl-1,10-phenanthroline, a metallic material and / or a bonding promoting material; is a layer obtained by co-evaporating The bonding promotion material is a compound selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum; The solar cell according to claim 1 .
6. The electron transport layer is provided on the active layer side of the junction promoting region. 60 Further comprising a fullerene-containing region comprising a fullerene or a derivative thereof. The solar cell according to claim 5 .
7. the adhesion promotion region contains the 9-bis(naphthalene-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalene-2-yl)-4,7-diphenyl-1,10-phenanthroline and a material constituting the cathode layer; The solar cell according to claim 1 .
8. The solar cell according to any one of claims 1 to 7, A sealing material that covers the solar cell; A solar cell module comprising:
9. Providing an active layer comprising a metal halide perovskite compound; forming an electron transport layer on the active layer; forming a cathode layer adjacent to and on the electron transport layer; Including, The step of forming the electron transport layer comprises: forming an electron transport material-containing region comprising 9-bis(naphthalen-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalen-2-yl)-4,7-diphenyl-1,10-phenanthroline; and forming a bonding-promoting region on the electronic material-containing region, the bonding-promoting region containing at least one compound selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum; A method for manufacturing solar cells.
10. The step of forming the electron transport layer comprises: Before the step of forming the electron transport material-containing region, 60 forming a fullerene-containing region comprising a fullerene or a derivative thereof; The method for producing a solar cell according to claim 9 .
11. The method further includes the step of heating at least the cathode layer and the electron transport layer to a temperature of 60° C. or higher and 180° C. or lower after the step of forming the cathode layer. The method for manufacturing a solar cell according to claim 9 or 10.
12. Providing an active layer comprising a metal halide perovskite compound; forming an electron transport layer on the active layer; forming a cathode layer adjacent to the electron transport layer; Including, The step of forming the electron transport layer comprises: co-depositing 9-bis(naphthalen-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalen-2-yl)-4,7-diphenyl-1,10-phenanthroline with a metal material and / or a bonding promotion material to form a bonding promotion region; The bonding promotion material is a compound selected from the group consisting of 8-quinolinolatolithium, lithium 2-(2',2''-bipyridin-6'-yl)phenolate, lithium 2-(isoquinolin-1'-yl)phenolate, lithium fluoride, lithium oxide, lithium acetate, and tris(8-quinolinolato)aluminum; A method for manufacturing solar cells.
13. The step of forming the electron transport layer comprises: Prior to the step of forming the adhesion-promoting region, 60 Further comprising the step of forming a region including fullerene or a derivative thereof. The method for producing a solar cell according to claim 12 .
14. Providing an active layer comprising a metal halide perovskite compound; forming an NBPhen layer containing 9-bis(naphthalene-1-yl)-4,7-diphenyl-1,10-phenanthroline and / or 9-bis(naphthalene-2-yl)-4,7-diphenyl-1,10-phenanthroline on the active layer; forming a metallic material layer adjacent to the NBPhen layer, the metallic material layer comprising a metallic material; After the step of forming the metal material layer, the step of heating the NBPhen layer and the metal material layer to 60° C. or more and 180° C. or less. A method for manufacturing solar cells.
15. After the step of preparing the active layer and before the step of forming the NBPhen layer, 60 Further comprising the step of forming a region including fullerene or a derivative thereof. The method for producing a solar cell according to claim 14 .